Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1080/15592324.2015.1010912
|View full text |Cite
|
Sign up to set email alerts
|

Linking pattern recognition and salicylic acid responses in Arabidopsis through ACCELERATED CELL DEATH6 and receptors

Abstract: The Arabidopsis membrane protein ACCELERATED CELL DEATH 6 (ACD6) and the defense signal salicylic acid (SA) are part of a positive feedback loop that regulates the levels of at least 2 pathogen-associated molecular patterns (PAMP) receptors, including FLAGELLIN SENSING 2 (FLS2) and CHITIN ELICITOR RECEPTOR (LYSM domain receptor-like kinase 1, CERK1). ACD6- and SA-mediated regulation of these receptors results in potentiation of responses to FLS2 and CERK1 ligands (e.g. flg22 and chitin, respectively). ACD6, FL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…c2 (Salleh et al, 2012) and is reported to confer tolerance to oxidative stress in yeast (Mowla et al, 2006). ACD6 and SYP122 are additional components of the salicylic acid-signaling network initiated during defense (Lu et al, 2003;Zhang et al, 2007Zhang et al, , 2008Tateda et al, 2015). Interestingly, both WRKY53 and SAG21 were also found to be up-regulated in trol mutants (Juri c et al, 2009).…”
Section: Oxidative Stress O 2 C2mentioning
confidence: 99%
“…c2 (Salleh et al, 2012) and is reported to confer tolerance to oxidative stress in yeast (Mowla et al, 2006). ACD6 and SYP122 are additional components of the salicylic acid-signaling network initiated during defense (Lu et al, 2003;Zhang et al, 2007Zhang et al, , 2008Tateda et al, 2015). Interestingly, both WRKY53 and SAG21 were also found to be up-regulated in trol mutants (Juri c et al, 2009).…”
Section: Oxidative Stress O 2 C2mentioning
confidence: 99%
“…Enhanced PAMP responses and SA signalling correlated with a protein accumulation of PRRs, such as FLS2, BAK1, CERK1, or ERF in microsomal fractions (Tateda et al, ; Tateda, Zhang, & Greenberg, ). Priming in chemically induced resistance caused systemic MPK3 and MPK6 gene expression as well as protein accumulation of the inactive (unphosphorylated) kinase form of MPK3 and MPK6 (Beckers et al, ).…”
Section: Systemic Sar Manifestationmentioning
confidence: 99%
“…acd6-1 and bda1-17D are both gain-of-function mutations located in the transmembrane regions, which cause spontaneous cell death and constitutive defense responses. ACD6 positively regulates the abundance of several PRRs (Tateda et al, 2015). It likely functions as a critical regulator of PTI.…”
Section: Autoimmunity Caused By Mutations In Other Types Of Proteinmentioning
confidence: 99%